Co-digestion of Shumblan with Different Wastes as a Source for the Biogas Production - Farhan, Duaa A.; Lattieff, Farkad A.; Atiya, Mohammed A. (Al-Khwarizmi Engineering Journal, 2018)
Shumblan (SH) is one of the most undesirable aquatic plants widespread in the irrigation channels and water bodies. This work focuses on boosting the biogas potential of shumblan by co-digesting it with other types of wastes without employing any chemical or thermal pretreatments as done in previous studies. A maximum biogas recovery of 378 ml/g VS was reached using shumblan with cow manure as inoculum in a ratio of 1:1. The methane content of the biogas was 55%. Based on volatile solid (VS) and C/N ratios, biogas productions of 518, 434, and 580 ml/g VS were obtained when the shumblan was co-digested with food wastes (SH:F), paper wastes (SH:P), and green wastes (SH:G) respectively. No significant changes of methane contents were observed during the anaerobic co-digestion of shumblan with the selected wastes. This noticeable increments of biogas yields proved that this sort of biomass can be utilized as a promising source for bioenergy production of industrial scale because of its economic operation. Slight pH variations indicated that the co-digestion performance has a good stability operation and no excessive amounts of volatile fatty acid were accumulated. The results also proved that by using co-digestion technology, the biodegradation of shumblan plants could be significantly accelerated supplying greater amounts of biogas yields. Moreover, the appropriate co-digestion with other wastes gave the shumblan high digestibility and, hence, there will be no need to prior pretreatment in order to boost the biogas yield.